Volcanic Ash Fall Hazard of Mount Merapi on Yogyakarta Nuclear Area - Setiaji, Abimanyu Bondan Wicaksono; Satyarno, Iman; Harijoko, Agung (EKSPLORIUM, 2022)
The existence of nuclear installations in the Yogyakarta Nuclear Area is vulnerable to the eruption of Mount Merapi, the most active volcano in Indonesia. Tephra hazard has the potential to threaten the operational activities of nuclear installations in the Yogyakarta Nuclear Area; thus, it is necessary to analyze the distribution and potential hazard of volcanic ash from Mount Merapi for future eruptions. Numerical modelling is used in analyzing tephra distribution using TEPHRA2 software with parameters of the 2010 Mount Merapi eruption, which is then visualized to isomass and isopach maps of tephra distribution. The analysis resulted in the ash dispersion leading to the Yogyakarta Nuclear Area in April, May, June, and August with an accumulated mass of 20-50 kg/m3 with a thickness of 0.2-12 cm. It is necessary to deal with volcanic ash hazards such as roof strength, secondary cooling system, filtering system, and electrical system for several installations in the Yogyakarta Nuclear Area.